2005
DOI: 10.1001/archopht.123.12.1684
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypoxemia and Hyperglycemia on pH in the Intact Cat Retina

Abstract: To examine the effects of acute hypoxemia and hyperglycemia on retinal pH to understand hyperglycemia-induced changes in the normal intact cat retina.Methods: Spatial profiles of extracellular hydrogen ion (H ϩ ) concentration were obtained from the cat retina, in vivo, using pH-sensitive microelectrodes during normoxia (arterial partial pressure of oxygen [PaO 2 ]=114.5±7.9 mm Hg), normoglycemia (plasma glucose concentration, 117 ± 19 mg/dL), acute hypoxemia (PaO 2 = 29.5 ± 2.2 mm Hg), and acute hyperglycemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…20 Animal and human studies support the relationship between hyperglycemia and circulatory retinal changes, which, in conjunction with hypoxemia, can accelerate the onset and progression of diabetic retinopathy. [21][22][23][24] Furthermore, it is well established that the prevention of proliferative retinopathy in diabetic adults requires the tightest possible glucose control. 22,25 A number of study limitations need to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…20 Animal and human studies support the relationship between hyperglycemia and circulatory retinal changes, which, in conjunction with hypoxemia, can accelerate the onset and progression of diabetic retinopathy. [21][22][23][24] Furthermore, it is well established that the prevention of proliferative retinopathy in diabetic adults requires the tightest possible glucose control. 22,25 A number of study limitations need to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…First, pH measurements on healthy cats showed that the retina acidified by more than 0.1 pH units during acute hyperglycemia (blood glucose >200 mg/dl). 12 Second, during hypoxemia the retina acidified, presumably from a compensatory increase in outer retinal glycolysis. 12 Inner retinal tissue hypoxia occurred in long-term diabetic cats, even in areas where capillary drop-out was not visible.…”
Section: Introductionmentioning
confidence: 99%
“…12 Second, during hypoxemia the retina acidified, presumably from a compensatory increase in outer retinal glycolysis. 12 Inner retinal tissue hypoxia occurred in long-term diabetic cats, even in areas where capillary drop-out was not visible. 1 It seemed possible that the chronic hyperglycemia and hypoxia caused by diabetes might lead to acidification of the retina and to alterations in glycolytic metabolism as well as other processes.…”
Section: Introductionmentioning
confidence: 99%
“…The function of retinal pericytes is known to be altered by elevated blood glucose, which might play a key role in regulation of vessel tone [14, 15]. The exact biochemical mechanism of how vascular endothelial cell function and the contractility of pericytes are modified needs to be defined, and this is subject of intensive research [16,17,18,19,20,21]. On the other hand, there is evidence that insulin itself and glycemic control might alter microcirculation during the therapy of hyperglycemia [13, 22, 23], and therefore it is important to note that the daily insulin dose of the 17 subjects reported here was increased during the study.…”
Section: Discussionmentioning
confidence: 99%